Curcumin Synergistically Enhances the Cytotoxicity of Arsenic Trioxide in U266 Cells by Increasing Arsenic Uptake. (12th October 2021) - Han, Dingding; Ma, Guibo; Gao, Yujuan; Su, Yanhua
Abstract : Despite the constant emergence of new methods for the treatment of multiple myeloma (MM), relapse and drug resistance still exist, especially in MM with p53 mutations. Arsenic trioxide (ATO) can be used in MM treatment, but this single drug has poor effectiveness and also side effects. Curcumin is a safe and effective compound that can enhance the anticancer effects of many drugs. Previous studies have suggested that tumor cell sensitivity to ATO is related to the intracellular arsenic content, and aquaporin 9 (AQP9) is the key factor that determines intracellular arsenic content. This study aimed to explore whether curcumin can increase ATO cytotoxicity in MM and whether the mechanism is related to the regulation of intracellular arsenic content. U266 was treated with ATO, curcumin, and their combination, and cell proliferation, apoptosis, and intracellular arsenic content were detected by CCK-8 assay, flow cytometry, and HPLC-ICP-MS, respectively. AQP9 mRNA and protein levels were detected by qPCR and western blotting. The levels of Mcl-1, Bcl-2, Bax, caspase-3, and cleaved caspase-3 protein were detected by western blotting. ATO-induced cytotoxicity to U266 occurred in a time- and dose-dependent manner, but the therapeutic efficacy at low drug concentrations was modest. The arsenic content in U266 was lower than that in NB4, and the arsenic uptake by U266 was concentration-dependent. The expression levels of AQP9 mRNA and AQP9 protein in U266 were lower than those in NB4. Curcumin significantly enhanced the lethality of ATO to U266. The arsenic content in U266 in the combined drug group increased significantly compared with ATO treatment alone. After curcumin treatment, the AQP9 mRNA and AQP9 protein expression levels in U266 also increased. Compared with the control group, the expression of antiapoptotic proteins Mcl-1 and Bcl-2 decreased, the expression of proapoptotic protein Bax increased, the ratio of Bax/Bcl-2 increased, and the expression of caspase-3 decreased and cleaved caspase-3 increased in the combined drug groups. Curcumin can enhance the killing effects of ATO on U266 by increasing the intracellular arsenic content, which may be related to the upregulation of AQP9 expression. The combination of these two drugs is expected to be a potential clinical treatment for MM.